Dominant Dendrobium officinale mycorrhizal partners vary among habitats and strongly induce seed germination in vitro - Zhang, Liyue; Rammitsu, Kento; Tetsuka, Kenshi; Yukawa, Tomohisa; Ogura-Tsujita, Yuki (Frontiers in Ecology and Evolution, 2022)
Dendrobium officinale (Orchidaceae) is an endangered epiphytic orchid that has been well studied as a medicinal plant. Although previous studies have shown that various fungal isolates promote D. officinale seed germination and seedling development in vitro, mycorrhizal associations among its wild populations remain poorly understood. In this study, we identified mycorrhizal fungi associated with D. officinale (36 individuals from six sites) using Sanger sequencing and compared fungal communities among sites and habitats (lithophytic vs. epiphytic individuals). Among the obtained sequences, 77 belonged to orchid mycorrhizal fungi (OMF), among which Tulasnellaceae accounted for 45.4% and Serendipitaceae for 28.9%. The Serendipitaceae operational taxonomic unit (OTU) SE1 was the most dominant partner, accounting for 26.8% of all detected fungal sequences, followed by a Tulasnellaceae OTU, TU27, which accounted for 15.5%. The relative frequencies of Serendipitaceae and Tulasnellaceae differed greatly between lithophytic and epiphytic individuals. Serendipitaceae accounted for 47.3% of the OMF sequences among lithophytes, and Tulasnellaceae for 90.9% among epiphytes. Mycorrhizal community composition also varied among sites. We further conducted in vitro symbiotic culture from seeds with six fungal isolates. Two Serendipitaceae and two Tulasnellaceae isolates, including SE1 and TU27, significantly promoted seed germination and seedling development. These results indicate that D. officinale is mainly associated with Tulasnellaceae and Serendipitaceae as its main fungal partners, which strongly induced seed germination and seedling development in vitro, suggesting their association with D. officinale through its life cycle.